Pengaruh Intervensi Psikoedukasi terhadap Kesiapan Menarche pada Remaja Putri di SD Negeri Gebangsari 01 - Raihana Nazifa Salsabila; Hernandia Distinarista; Apriliani Yulianti Wuriningsih; Sri Wahyuni (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Menarche is a critical developmental milestone that often generates anxiety and maladaptive perceptions among adolescent girls when adequate preparedness is lacking. This study examined the effect of psychoeducational intervention on menarche readiness among female students at SD Negeri Gebangsari 01 using a school-based quasi-experimental one-group pretest–posttest design. The study involved 45 fourth- and fifth-grade female students selected through total sampling. Menarche readiness was measured using a validated and reliable ordinal-scale questionnaire, and data were analyzed using the Wilcoxon signed-rank test to assess within-subject changes. The findings demonstrated a significant increase in mean readiness scores from pretest to posttest, accompanied by a shift toward higher readiness categories and reduced variability in responses. Statistical analysis confirmed a significant difference between pre-intervention and post-intervention readiness levels (p < 0.05), indicating that the observed changes were attributable to the psychoeducational intervention. These results suggest that structured psychoeducation effectively enhances cognitive and emotional preparedness for menarche among primary school girls. The study highlights the strategic role of schools as early intervention settings for reproductive health education and supports the integration of psychoeducational programs into elementary school health promotion initiatives.